2022
DOI: 10.3389/fonc.2022.850155
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Sanyin Formula Plus Chemotherapy on Survival in Women With Triple-Negative Breast Cancer: A Randomized Controlled Trial

Abstract: PurposeTo evaluate the efficacy of the Sanyin formula (SYF) plus conventional standard chemotherapy in operable triple-negative breast cancer (TNBC) patients, a randomized controlled trial was implemented at 5 hospitals and cancer centers in China between May 23, 2016, and October 31, 2019.Materials and MethodsFemale patients aged 18 to 80 years with operable TNBC after definitive surgery were screened and enrolled. The exclusion criteria included metastatic disease, other tumors, or locally advanced disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…We found that SYF extract significantly inhibited the expression of MMPs in breast cancer cells, suggesting that SYF can effectively inhibit the metastasis of breast cancer. The results of the present study help to explain our previous clinical finding that additional DFS benefits were obtained with SYF plus chemotherapy compared with chemotherapy alone [ 13 ]. Our previous exploratory subgroup analysis showed that the benefit of SYF in patients with node-negative breast cancer was significantly higher than that in patients with node-positive breast cancer, which seemed to be achieved by SYF through the inhibition of MMPs to prevent breast cancer cell metastasis [ 13 ].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…We found that SYF extract significantly inhibited the expression of MMPs in breast cancer cells, suggesting that SYF can effectively inhibit the metastasis of breast cancer. The results of the present study help to explain our previous clinical finding that additional DFS benefits were obtained with SYF plus chemotherapy compared with chemotherapy alone [ 13 ]. Our previous exploratory subgroup analysis showed that the benefit of SYF in patients with node-negative breast cancer was significantly higher than that in patients with node-positive breast cancer, which seemed to be achieved by SYF through the inhibition of MMPs to prevent breast cancer cell metastasis [ 13 ].…”
Section: Discussionsupporting
confidence: 75%
“…The results of the present study help to explain our previous clinical finding that additional DFS benefits were obtained with SYF plus chemotherapy compared with chemotherapy alone [ 13 ]. Our previous exploratory subgroup analysis showed that the benefit of SYF in patients with node-negative breast cancer was significantly higher than that in patients with node-positive breast cancer, which seemed to be achieved by SYF through the inhibition of MMPs to prevent breast cancer cell metastasis [ 13 ]. This finding further proves the effectiveness of MMP inhibitors in the treatment of breast cancer metastasis.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations